2000
DOI: 10.1016/s0955-5986(00)00005-4
|View full text |Cite
|
Sign up to set email alerts
|

Installation effects on an ultrasonic flow meter with implications for self diagnostics

Abstract: A small ultrasonic flow meter for water was exposed to five different test configurations, a reference experiment, a single elbow, a double elbow out of plane, a reduction in pipe diameter and a pulsating flow experiment. All tests were performed in a flow calibration facility ranging over Reynolds number from 25 to 110 000. The experiments with the four installation effects were compared with a reference experiment. The error and the change in standard deviation compared to the reference experiment were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…(15) was below approximately 0.15, justifying therefore the choice of the RNG K − model. Additionally, the RNG K − model also requires less computational effort than the (13)…”
Section: Turbulence Closurementioning
confidence: 99%
See 1 more Smart Citation
“…(15) was below approximately 0.15, justifying therefore the choice of the RNG K − model. Additionally, the RNG K − model also requires less computational effort than the (13)…”
Section: Turbulence Closurementioning
confidence: 99%
“…The authors use Laser Doppler Anemometry (LDA) to recover complete information on the velocity components of disturbed profiles. Carlander and Delsing [13] performed a series of experiments comparing the standard deviation of ultrasonic flow measurements under disturbed condition against a reference condition. The authors found that, depending on the disturbance, the standard deviation can increase by up to more than 100%.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when there is flow of fluid in the pipe, the frequency of the reflected wave will be different. This is because of phenomena called as Doppler Effect [36]. The faster the fluid flows, the frequency shift will increases linearly.…”
Section: Coriolis Mass Flow Metersmentioning
confidence: 99%
“…However, swirling flow may also be a spurious effect, for example in flow measurement applications where an undisturbed fully developed flow profile may be favorable to achieve a small measurement error and good repeatability. Flow sensors are commonly tested with swirling flow conditions to assess their robustness (see, for example, Carlander and Delsing [1] and Wendt [2]). In such experiments, the flow patterns introduced by disturbance generators emulate flow disturbances caused by installation effects often found in pipe configurations, such as bends, junctions, and valves.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main difficulties in investigating the reproducibility experimentally: (1) In practice, it is difficult to separate reproducibility contributions from the swirling flow field from intrinsic reproducibility contributions of the flow sensor under test and (2) to reliably assess reproducibility of such tests, a large set of experiments would be required.…”
Section: Introductionmentioning
confidence: 99%